Time-variation in the Impact of News Sentiment - Smales, Lee (Elsevier BV, 2015)
Utilizing firm-specific news sentiment data provided by Thomson Reuters News Analytics, I construct aggregate measures to examine the relationship between news sentiment and stock market returns over the period 2004–2010. I find a highly significant relationship between aggregated measures of news sentiment and stock returns that fluctuates over time and by industry. I identify a link between the time-variation of news sentiment impact and industry beta, and determine that levels of investor sentiment (proxied by VIX) play an important role in explaining this variation.